Answer: Always true
Step-by-step explanation:
On the left side we have 4x+3x turn into 7x. The -12 stays as it is because it has nothing to pair with. The left side simplifies to 7x-12
The right side simplifies to 7x-12 as well because the like terms 5 and -17 combine to 5+(-17) = 5-17 = -12.
The original equation 4x-12+3x = 5+7x-17 has both sides simplify to 7x-12=7x-12. Both sides are identical which makes the original equation always true. No matter what number you replace x with, both sides will be the same result.
For instance, let's try x = 0
4x - 12 + 3x = 5 + 7x - 17
4(0) - 12 + 3(0) = 5 + 7(0) - 17
0 - 12 + 0 = 5 + 0 - 17
-12 = -12